Phytate in pig and poultry nutrition. Issue 4 (18th November 2014) - Humer, E.; Schwarz, C.; Schedle, K.
Summary Phosphorus (P) is primarily stored in the form of phytates in plant seeds, thus being poorly available for monogastric livestock, such as pigs and poultry. As phytate is a polyanionic molecule, it has the capacity to chelate positively charged cations, especially calcium, iron and zinc. Furthermore, it probably compromises the utilization of other dietary nutrients, including protein, starch and lipids. Reduced efficiency of utilization implies both higher levels of supplementation and increased discharge of the undigested nutrients to the environment. The enzyme phytase catalyses the stepwise hydrolysis of phytate. In respect to livestock nutrition, there are four possible sources of this enzyme available for the animals: endogenous mucosal phytase, gut microfloral phytase, plant phytase and exogenous microbial phytase. As the endogenous mucosal phytase in monogastric organisms appears incapable of hydrolysing sufficient amounts of phytate‐bound P, supplementation of exogenous microbial phytase in diets is a common method to increase mineral and nutrient absorption. Plant phytase activity varies greatly among species of plants, resulting in differing gastrointestinal phytate hydrolysis in monogastric animals. Besides the supplementation of microbial phytase, processing techniques are alternative approaches to reduce phytate contents. Thus, techniques such as germination, soaking and fermentation enable activation of naturally occurring plant phytase among others. However, further research is needed to tap the potential of these technologies. The main focus herein is to review the available literature on the role of phytate in pig and poultry nutrition, its degradation throughout the gut and opportunities to enhance the utilization of P as well as other minerals and nutrients which might be complexed by phytates.